2019
DOI: 10.4236/ojopm.2019.94004
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx Mori Chitosan Nanoparticles: Synthesis and Properties

Abstract: A synthesis of nanochitosan from Bombyx mori chitosan with particle sizes of 20-100 nm was carried out. The antibacterial and immunological properties of synthesized nanochitosan were first studied. It was revealed that preparations based on nanochitosan have pronounced antibacterial activity, and are also able to significantly increase the immune response of the living system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Chitin bleaching was the last process, and the output dropped to 3.6%. Original chitin samples were crystallized between 76 and 86%, based on the yield of each sample [171].…”
Section: Silkwormmentioning
confidence: 99%
“…Chitin bleaching was the last process, and the output dropped to 3.6%. Original chitin samples were crystallized between 76 and 86%, based on the yield of each sample [171].…”
Section: Silkwormmentioning
confidence: 99%
“…The present study focuses on the utilization of chitosan nanopowder with a size range of 80–100 nm. The selection of this particular size range is based on the previous research conducted by Milusheva et al (2019) [ 55 ], where chitosan nanopowder with a size range of 20–100 nm was isolated from Bombyx mori Linnaeus insect. The research findings suggested a significant enhancement in the immune response of the living system.…”
Section: Introductionmentioning
confidence: 99%